Copper-Catalyzed Annulation–Cyanotrifluoromethylation of 1,6-Enynes Toward 1-Indanones via a Radical Process - Zhang, Tian-Shu; Hao, Wen-Juan; Cai, Pei-Jun; Li, Guigen; Tu, Shu-Jiang; Jiang, Bo (Frontiers in Chemistry, 2020)
A new Cu(II)-catalyzed annulation-cyanotrifluoromethylation of 1,6-enynes with Togni's reagent and TMSCN has been established, enabling the direct construction of trifluoromethylated 1-indanones with an all-carbon quaternary center in good yields. This reaction was performed by using low-cost Cu(OTf)2 as the catalyst and Togni's reagent as both the radical initiator and a CF3 source, providing an efficient protocol for building up 1-indanone framework with wide functional group compatibility. The reaction mechanism was proposed through a radical triggered addition/5-exo-dig cyclization/oxidation/nucleophilic cascade.